Planning for a Disrupted Future: Modeling the Effects of Sea Level Rise on Endangered Shorebird Habitat on Nantucket Island - McCarthy, Jarrod. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Jon Witten.; Committee: Sumeeta Srinivasan.; Keywords: Land use planning, Conservation biology, and Wildlife management.